The Dual Effect of Tolvaptan on Diuresis and Azotemia in a Case of Acute Kidney Injury with Furosemide Resistance After Coronary Artery Bypass Grafting: A Case Report - Supriyadi, Eddo; Karseno Dibyosubroto, Iradewi; Sugiarto, Adhrie (Writing Center IMERI FMUI, 2025)
Background: Acute kidney injury (AKI) after coronary artery bypass grafting (CABG) affects up to 30% of patients, increasing morbidity and mortality. Increasing Furosemide dose, by blocking sodium, potassium, and chloride reabsorption, paradoxically increases urea reabsorption to maintain medullary osmolarity. This increased urea retention reduces Furosemide’s effectiveness and can elevate urea levels. Tolvaptan, a V2 receptor antagonist, indirectly inhibits Urea Transporter A1 (UT-A1), potentially opposing this effect. Case Presentation: A 67-year-old man post-CABG developed inadequate diuresis despite high-dose Furosemide (20 mg/hour). Post-extubation, he experienced worsening dyspnea, positive fluid balance, elevated Central Venous Pressure (CVP), and a sharp rise in creatinine (0.97 to 4.74 mg/dL). Dialysis was planned on Day 3 but deferred for observation after initiating Tolvaptan. Following Tolvaptan administration, diuresis improved, CVP decreased, and Creatinine fell to 2.11 mg/dL. The patient recovered without further events. Discussion: This case describes the potential use of Tolvaptan as an adjunct to Furosemide to improve diuresis and decrease urea reabsorption. Furosemide improves diuresis by blocking electrolyte reabsorption, but this effect is often counteracted by a compensatory increase in urea reabsorption to maintain peritubular tissue osmolarity, which lowers the overall potency of the diuretic. This water retention, coupled with increased sodium chloride in the tubule, triggers the macula densa and juxtaglomerular feedback, thus lowering GFR. Conclusion: Tolvaptan's potential to augment diuresis and improve urea removal is beneficial to reduce the need for dialysis. Further study is needed to confirm this theoretical application in other clinical settings.